Comparison of metabolomic profiles obtained using chemical ionization and electron ionization MS in exhaled breath. (December 2011) - Turner, MA; Guallar-Hoyas, C; Kent, AL; Wilson, ID; Thomas, CLP
The exhaled breath is rich in a wide range of volatile organic compounds with the potential to provide readily accessible biomarkers for metabolic activity in the body as a result of normal or abnormal/disease processes. Exhaled breath samples from five healthy volunteers have been analyzed by thermal desorption GC–MS using electron impact and chemical ionization. A total of eight compounds: 2-propenoic acid; 2-methyl, methyl ester; toluene; hexanal; 1, 4-cyclohexadiene, 1-methyl-4-(1methlethyl); phenol; nonanal; dodecane and indole, have been evaluated to establish differences in selectivity and sensitivity using these two mechanisms of ionization. The combination of both electron impact and chemical ionization profiles could prove valuable when prospecting for breath-derived biomarkers as they result in complementary information that aids the identification of unknown components.